AB0913 Influence of Oral Prednisolone on Effect of Denosumab on Osteoporosis in Patients with Japanese Rheumatoid Arthritis: A Multicenter Registry Study. (9th June 2015) - Kanayama, Y.; Hirano, Y.; Asai, S.; Hirabara, S.; Kojima, T.; Ishiguro, N.
Abstract : Background: Denosumab (DMB) is a fully human monoclonal antibody to the receptor activator of nuclear factor-kappaB ligand (RANKL) that blocks its binding RANK, inhibiting the development and activity of osteoclasts, decreasing bone resorption, increasing bone density and reducing fracture risk. Osteoporosis (OP) is more frequent in patients with rheumatoid arthritis (RA) than in the general population due to active systemic inflammation as well as the use of glucocorticoid and immobility. However efficacy of denosmab is not clear in patirnts with glucocorticoid- induced OP in RA. Therefore we investigated the influence of oral prednisolone on effect of DMB in patients with Japanese RA from initiation to 6 months at this time. Objectives: This prospective study investigated the efficacy of DMB for 6 months on glucocorticoid- induced OP in RA patients. Methods: Patients with a diagnosis of RA according to the 2010 ACR/EULAR criteria who had been prescribed DMB from Tsurumai Biologics Communication Registry (TBCR)-BONE between October 2013 and April 2014 were enrolled. The final study cohort of 35 patients received continuous DMB therapy more than 6 months. The DMB dose was 60mg at once every 6 months. In all cases native or activated vitamin D has been used. We reviewed the results for 6 months about the increase and decrease of bone mineral density (BMD) of lumbar spine (LS) and total hip (TH) by DEXA and bone turnover markers, intact n-terminal propeptide type I procollagen (PINP) and tartrate-resistant acid phopshatate form 5b (TRACP-5b). Results: In the patients not receiving oral prednisolone group (n=19, N-PSL) and receiving group (n=16, R-PSL), the number of female was each 17 (89%) and 14 (88%) cases (p=0.855). The mean age was 70.9±9.0 and 67.6±7.3 years old (p=0.127); disease duration was 15.8±14.0 and 12.1±6.9 years (p=0.679); the body mass index was 19.4±2.6 and 20.0±4.1 (p=0.987) and the FRAX was 23.6±12.9 and 25.4±14.5 (p=0.827). Clinical findings related to RA and OP at baseline were as follows; CRP 0.2±0.3 and 1.0±1.5 mg/dl (p=0.043); DAS-CRP 1.93±0.76 and 2.72±0.95 (p=0.014); m-HAQ 0.63±0.70 and 1.23±0.94 (p=0.023); PINP 58.3±31.5 and 63.1±43.9 μg/l (p=0.869); TRACP-5b 498±212 and 562±281 mU/dL (p=0.643); LS-BMD 0.78±0.15 and 0.86±0.2 g/cm 2 (p=0.120) and TH-BMD 0.59±0.07 and 0.62±0.12 g/cm 2 (p=0.426). The rate of decreased PINP and TRAC-5b from baseline to 6 months were each 55.9% vs 27.4% (p=0.115) and 49.2% vs 39.5% (p=0.986) in the N-PSL group vs R-PSL group. The rate of increased LS-BMD and TH-BMD from baseline to 6 months were each 4.5% vs 4.7% (p=0.899) and 3.6% vs 2.9% (p=0.406) in the N-PSL group vs R-PSL group. The numbers of patients who did not increase LS-BMD and TH-BMD for 6 months were each 2 (11%) vs 4 (27%) cases (p=0.375) and 3 (17%) vs 2 (13%) cases (p=0.790) in the N-PSL group vs R-PSL group. Conclusions: DMB was effective in OP of RA patients. Oral prednisolone use did not influence the efficacy of DMB in the short period of 6 months. Disclosure of Interest: Y. Kanayama: None declared, Y. Hirano Speakers bureau: Abbott Japan Co. Ltd.; Eisai Co. Ltd.; Mitsubishi Tanabe Pharma Corporation; Pfizer Co. Ltd.; Chugai Pharmaceutical Co. Ltd.; and Bristol-Myers Squibb Co. Ltd., S. Asai: None declared, S. Hirabara: None declared, T. Kojima Speakers bureau: Abbott Japan Co. Ltd.; Eisai Co. Ltd.; Mitsubishi Tanabe Pharma Corporation; Pfizer Co. Ltd.; Chugai Pharmaceutical Co. Ltd.; and Bristol-Myers Squibb Co. Ltd., N. Ishiguro Speakers bureau: Abbott Japan Co. Ltd.; Eisai Co. Ltd.; Mitsubishi Tanabe Pharma Corporation; Pfizer Co. Ltd.; Chugai Pharmaceutical Co. Ltd.; and Bristol-Myers Squibb Co. Ltd.